STABILITY OF THE STRAINS OF BASIDIOMYCETES DURING STORAGE IN THE COLLECTION - S. Miros; v. Koocherov; S. Bilokon; A. Sechnyak (Harčova Nauka ì Tehnologìâ, 2020)
Basidial macromycetes may be a material for the development of new biotechnologies, medical preparations, components of dietary nutrition. Therefore, it is necessary for the highest level of quality for maintenance and identification of mushroom strains in the collection. An important parameter, in this case, is a stability of isolated and described collection strains of basidiomycetes. Stability is one of the key issues of long-term preservation of pure culture collections. For the collection of medicinal basidiomycetes of ONU I.I. Mechnikov, which preserves by the method of periodic reseeding of colonies the strain stability had not been studied yet. The goal of this research is to study the stability of this collection by a growth rate of mushroom colonies and electrophoretic spectra of carboxylesterases after different times of storage of cultures on malt agar. In this research the strains of three age categories (1, 2 and 3 years) of storage on malt-agar medium at temperature 4 ° С for were tested. The radial growth rate of their vegetative mycelium and the spectra of multiple molecular forms of carboxylesterases by the method of vertical electrophoresis in 7% of polyacrylamide gel were investigated. It was established that the stability of the radial growth rate of A. auricula-judae, F. velutipes, G. lucidum the vegetative mycelium after different storage periods is high according to the values of variation coefficients. At the same time, the expression of molecular forms of carboxylesterase showed sufficient variability. Partially conservative molecular forms were detected in some age groups of strains, as well as for individual strains. Thus the growth rate of colonies is a stable indicator and the molecular forms of carboxylesterases of different ages strains are variable.